Standar Biaya Operasi Non Personalia Jenjang Pendidikan SMA/SMK di Provinsi Kalimantan Tengah : Penelitian - Winaryo, Slamet; Radiafilsan, Christian; Nugroho, Piter Joko (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study analyzes the strategy for meeting and the amount of non-personal operating costs (BOPNP) at senior high schools (SMA) and vocational high schools (SMK) in Central Kalimantan Province as a basis for establishing realistic and fair regional cost standards. The research background indicates that the Regular BOS funds are insufficient to cover operational needs, particularly for technology-based learning, facility maintenance, and non-ASN staff honoraria. Using a descriptive qualitative approach, 2021 data was collected through online interviews, observations, and documentation studies of 63 SMA and SMK principals in various regions. The results show that schools implement adaptive financing strategies that are structural, participatory, and collaborative, yet more than 87% remain underfunded, with BOS only covering 45–55% of actual needs. SMA BOPNP needs range from Rp2,750,000–Rp3,500,000 per student per year, and SMK Rp3,500,000–Rp4,750,000, influenced by geographic factors, activity complexity, and low community support due to negative perceptions of levies. The research confirms the need to re-establish the Regional Cost Index-based SBONP to ensure equitable education quality. These findings form the basis for developing a contextual, transparent Regional Operational Assistance (BOSDA) program that is focused on improving the quality of secondary education services.